Spain : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that Spain experienced a second year of subdued growth in 2002-albeit at a rate still well above the euro area average. This was largely owing to the relative resilience of Spain's domestic demand, which in turn was supported by a comparatively stronger showing of investment, sustained by booming construction activity and a continued public infrastructure effort. After having been the mainstay of the earlier upswing, private consumption lost momentum, as households coped with rising inflation and higher indebtedness.